Higher education for sustainable development in the digital era: Mapping the bibliometric analysis - Zhavoronok, А.; Kholiavko, N.; Popelo, O.; Dubyna, M.; Verbivska, L.; Fedyshyn, M. (Problems and Perspectives in Management, 2024)
Modern higher education institutions in developed countries are becoming active agents of permanent societal changes. The aim of the study is to map the scientific landscape on the topic of higher education for sustainable development in the context of digitalization. In the research process, bibliometric analysis, an in-built Scopus instrument, and VOSviewer were used. The findings proved that the severe restrictions faced by universities during the COVID-19 pandemic became a powerful impulse to intensify the attention of scientists to the mentioned topic. Visualization maps of keywords and scientific publications showed the existing interdisciplinary nature and the main thematic directions of research on higher education for sustainable development in the digital era. They demonstrated a direct connection between the basic principles of the sustainable development concept, sustainable development goals, higher education, universities, digitization, and digital technologies. The largest number of works on the specified subject belong to scientists from China, Spain, the Czech Republic, Germany, and Ukraine. The study concluded that future publications in the analyzed field would cover the effectiveness of digital technologies in higher education, the development of competencies for the digital economy, inclusiveness, cybersecurity, as well as ethical aspects of the use of technologies to achieve the global sustainable development goals.
Keywords: higher education, university, sustainable development concept, sustainable development goals, digitization, digital technologies, bibliometric analysis